APLIKASI CVT PADA SEPEDA MOTOR LISTRIK (SEMOLI) GENERASI 2 - Girawan, Bayu Aji; Nur Akhlis Sarihidaya Laksana; Unggul Satria Jati (Politeknik Negeri Cilacap, 2024)
The trend of using electric motorbikes to drive two-wheeled vehicles in Indonesia has started to increase. This is because the increasing public awareness of the benefits of electric vehicles is linked to the decreasing fossil energy reserves. Apart from that, electric vehicles are an environmentally friendly means of transportation because they do not cause air pollution. Based on previously research SEMOLI Generation 1, it is known that the use of a sprocket and chain transmission model on electric motorbikes produces less than optimal performance when used on flat roads, because on flat roads there is no need for large torque. The aim of this SEMOLI Generation 2 research is to conduct experiments using a CVT transmission which is predicted to be able to provide large torque when the road conditions are uphill, and able to provide higher speeds when the road conditions are flat. The research stages carried out successively are: conducting studies, selecting transmissions, assembling, fabricating, designing frames and swing arms, testing, and preparing documents. Based on the test results, it was found that using a CVT was able to increase maximum speed on both horizontal and uphill road conditions. This increase is because CVT has a wide transmission comparison range, so it is able to overcome uphill and horizontal road conditions.